A fuzzy function of C-level subsets. (18th August 2021) - AL-Hur Kadum, Intissar Abd; Abdulwahab, Azal Taha; Alkfari, Batool Hatem Akar
Abstract: The definition of fuzzy function concept as a function of the fuzzy C-level of the elements of fuzzy sets is considered the main goal of this work. The research is composited as follows : In section 1, we define the fuzzy concept, in section 2, we introduce basic information about extension principle and fuzzy sets. However, fuzzy function of the fuzzy C-level and a related fuzzy function to this concept are investigated and some significant results are proved in section 3.